Swiss finance : capital markets, banking, and the Swiss value chain - Meier, Henri B. (Robert W. Kolb series in finance., 2013)
"A timely guide to the complex financial markets and banking secrecy of Switzerland since 1934, when Switzerland's federal bank secrecy law was passed, the line between myth and reality with regard to Swiss banking has been blurred. But over the past decade, there have been dramatic changes in the pressures brought to bear on all facets of the Swiss financial markets and banking sector. Recent developments and agreements have potentially weakened Swiss banking secrecy, and with that said, it is time for a book that lays out the history of Swiss bank secrecy and puts these twenty-first century changes in perspective. Swiss Finance is a thorough overview of the Swiss financial markets and the banking secrecy this country has become known for. It covers key topics to practitioners both abroad and in the United States involved in Swiss banking and the Swiss financial markets. Discusses what the Euro-debt crisis may mean for the role of Switzerland as a financial powerhouse Reveals how new secrecy agreements with the United States and Germany will impact private wealth management Addresses Asian competition for wealth management and tax havens Switzerland is one of the largest financial markets in the world and a global power in private wealth administration. Whether you're a private wealth advisor, Swiss or U.S. banker, or other finance practitioner involved in the Swiss market, this guide is essential reading if you intend on achieving future success in this arena"--